1999
DOI: 10.1037/0278-7393.25.4.942
|View full text |Cite
|
Sign up to set email alerts
|

Rate of forgetting in amnesia: I. Recall and recognition of prose.

Abstract: Three experiments explored the rate at which amnesic participants' free recall, cued recall, and recognition of prose declined over short filled delays. In Experiment 1, after performance had been matched to that of controls at 15s, amnesics showed accelerated forgetting over delays of up to 10 min in a free-recall condition, whereas recognition performance declined normally over delays of up to 1 hr. This pattern of results was replicated in Experiment 2, which showed that amnesic rate of forgetting on a test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
71
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(82 citation statements)
references
References 44 publications
(67 reference statements)
10
71
1
Order By: Relevance
“…The evidence arising from the present study that amnesics are more susceptible to part-list cuing than healthy subjects is not in conflict with previous results in which it was found that amnesics show normal retroactive and proactive interference (Isaac & Mayes, 1999a;Warrington & Weiskrantz, 1978). Rather, it is consistent with the view that interference and part-list cuing are mediated by different mechanisms (Anderson et al, 2000;D.…”
Section: Part-list Cuing Versus Interferencecontrasting
confidence: 52%
See 1 more Smart Citation
“…The evidence arising from the present study that amnesics are more susceptible to part-list cuing than healthy subjects is not in conflict with previous results in which it was found that amnesics show normal retroactive and proactive interference (Isaac & Mayes, 1999a;Warrington & Weiskrantz, 1978). Rather, it is consistent with the view that interference and part-list cuing are mediated by different mechanisms (Anderson et al, 2000;D.…”
Section: Part-list Cuing Versus Interferencecontrasting
confidence: 52%
“…Storage deficit proposals assume that amnesic patients show a deficit in the initial consolidationof episodic material into long-term memory. This deficit is assumed to arise mainly in the case of the consolidation of complex associations and less, if at all, in the consolidation of simple associations and information (Isaac & Mayes, 1999a, 1999b. Proposals emphasizing deficits in the encoding-retrieval interaction assume that amnesic patients have trouble encoding the features of material in such a way that cues directed toward feature representation can evoke the desired item directly.…”
mentioning
confidence: 99%
“…These two sources of evidence indicate that the duration of verbal short-term memory is less than 15 seconds. Therefore, if similar mechanisms underlie visuo-spatial short-term memory it is unlikely that it is still contributing to performance after 20 seconds (see Downes et al, 1998;Isaac and Mayes, 1999, for a discussion of these issues). If this is the case, the accelerated forgetting shown by NM is most likely to be due to a consolidation deficit.…”
Section: Discussionmentioning
confidence: 99%
“…This latter explanation is unlikely, at least for patient NM, whose performance was still matched to the controls at 20 seconds, but who showed accelerated forgetting between this delay and 60 seconds. Although the duration of visual short-term memory has not been established, the duration of verbal short-term memory was estimated by experimental methods to be two seconds or less (Muter, 1980) when rehearsal is not possible and amnesic patients with normal short-term memory (assessed by digit span) were severely impaired at verbal recall after a filled delay of only 15 seconds (Isaac and Mayes, 1999). These two sources of evidence indicate that the duration of verbal short-term memory is less than 15 seconds.…”
Section: Discussionmentioning
confidence: 99%
“…These include: (1) the need to 'match' the starting point from which forgetting is measured; (2) the advantages/disadvantages of different techniques for this matching; (3) avoiding ceiling and floor effects; (4) consideration about whether forgetting should start being measured during or immediately following stimulus presentation; (5) the nature of the distraction activity between test intervals; and (6) whether repeated or equivalent material should be tested at different delay intervals (Brooks & Baddeley, 1976;Green & Kopelman, 2002;Huppert & Piercy, 1977, 1978Isaac & Mayes, 1999a, 1999bKopelman, 1985Kopelman, , 1997Kopelman, , 2000bKopelman & Stanhope, 1997;Mayes, 1988;Mayes & Downes, 1997;McKee & Squire, 1992;Slamecka & McElree, 1983). Reviewing the epilepsy literature, Elliott, Isaac, and Mulhert (2014) published a methodological critique of forgetting studies, which additionally included comments on the need to use both verbal and visual forgetting measures, and the importance of appropriate matching of groups on demographic and cognitive variables.…”
Section: Accepted Manuscriptmentioning
confidence: 99%